Cause Analysis of an Infection in Facelift Surgery Due to Mycobacterium chelonae - Decalonne, Marie; Lecorche, Emmanuel; Hau, Estelle; Petiteau, Agnès; Moreau, Célia; Milan, Odile; Lanotte, Philipe; Mereghetti, Laurent; Cambau, Emmanuelle; van der Mee-Marquet, Nathalie (Frontiers in Medicine, 2019)
We report a post-facelift infection due to Mycobacterium chelonae. Based on the analysis of the whole genome sequences of the clinical strain and an environmental strain recovered from the water supply network of the surgical clinic, the infection likely occurred following contamination of the unhealed wound with M. chelonae while showering at day 1 at the clinic, and durable exposure of the colonized wound to the moist and warm working conditions of a bakery from day 2.